Tingkat Pengetahuan Pasien dan Keluarga tentang Hak dan Kewajiban di Rumah Sakit X - Fauziah, Rachmania Syifa; Sugiarti, Ida (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
All healthcare facilities, including hospitals, are responsible for providing clear information regarding patients’ rights and obligations. A preliminary study at Hospital X revealed that staff did not fully explain the rights and obligations stated in the general consent form, but only gave a brief overview of the right to receive effective and efficient services and the obligation to comply with hospital regulations. This study aims to describe the knowledge of patients and their families regarding the rights and obligations outlined in the general consent form at Hospital X in 2025. Using a quantitative descriptive design with 100 respondents selected through accidental sampling, data were collected via questionnaires and analyzed descriptively. The results showed that 40% of respondents had good knowledge, 27% had moderate knowledge, and 33% had poor knowledge. These findings suggest that inpatient registration officers should provide a complete explanation of patients’ rights and obligations to ensure patients and their families have a clear understanding. Additionally, it is recommended that hospitals assign dedicated officers to handle the general consent process apart from inpatient registration staff to ensure that information regarding patients’ rights and obligations is effectively communicated.